BUSINESS TRAINING DEVELOPMENT MODEL THROUGH THE BASED LEARNING PROJECT IN STUDENTS - Hastuti, Indra; Utami, Indah Wahyu (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
his research was conducted aiming to find a model of developing entrepreneurship training through a Project Based Learning approach based on contextual business problems, applying planned businesses in real terms. This model is expected to be a form of community based education (fostering active participation of students in education and training) that is able to form new entrepreneurs to benefit, create jobs to reduce unemployment and poverty in Indonesia. This study uses qualitative research methods with a simulation observation research strategy. Observations were made on student business pilot groups, each group consisting of 4-5 students taking the Entrepreneurship course. The results obtained by the development model of entrepreneurship training in students. From the results of the entrepreneurship mapping, students can plan businesses according to their interests and expertise and through the training development model students can solve problems in business plans related to leadership, courage in taking risks, perseverance to focus on doing work, the level of discipline so students can successfully build businesses new business. Keywords: Model, training, business plan, entrepreneurship